Carbon fibers for treatment of cancer metastasis in bone. Issue 55 (7th September 2020) - Kamanaka, Takayuki; Haniu, Hisao; Tanaka, Manabu; Takizawa, Takashi; Aoki, Kaoru; Okamoto, Masanori; Sobajima, Atsushi; Yoshida, Kazushige; Ideta, Hirokazu; Mimura, Tetsuhiko; Ishida, Haruka; Ueda, Katsuya; et al.
Abstract : Local administration of cisplatin-conjugated carbon fibers is expected to become the first therapy to suppress cancer growth with low prevalence of adverse reactions, and to repair bone damaged by metastasis. Abstract : When cancer metastasizes to bone, the resulting pain and functional disorders due to bone destruction adversely affect the patient's quality of life. We have developed a new cancer metastasis control system consisting of anticancer agents conjugated to carbon fibers (CFs), which are nonbiodegradable, carriers of a wide variety of molecules with extremely high affinity for bone. In the evaluation of cancer suppression effects on Walker 256 cancer cells, cisplatin (CDDP)-conjugated CFs (CF-CDDP) were found to be as effective in cancer suppression as CDDP. In the evaluation of the cancer suppression effects of local injection in the rat model of tibial cancer bone metastasis, similar cancer suppression was noted in the CF-CDDP group and CDDP group; however, blood Pt concentrations were significantly lower in the CF-CDDP group. Experiments with CDDP and CF-CDDP injected into bone actually destroyed by cancer metastases revealed the presence of significantly more newly formed bone tissue with the administration of CF-CDDP. Local administration of CF-CDDP is expected to become the first therapy to suppress cancer growth with low prevalence of adverse reactions, and to repair bone damaged by metastasis.